Answer:
D
Step-by-step explanation:
Since they are the same variables
Answer:
C. In y^2-y=6, 6 should have been subtracted on both sides first.
Step-by-step explanation:
It is a quadratic equation so you subtract the 6 and create
y^2-y-6=0
Then you factor it to:
(y-3)(y+2)=0
The solutions then are:
y-3=0, y=3 and y+2=0, y=-2
{-2,3}
Answer:
5.25 + 2.50 = 7.75. 10 - 7.75 =2.25
Step-by-step explanation:
I converted the four months into a fraction, and got 1/3. There's 12 months in a year, and divided by 4, I got 3.